Cult of Defeat in Mexico’s Historical Fiction - Price, B. author. aut Link
X, 189 p.
Keywords: Cult of Defeat in Mexico's Historical Fiction: Failure, Trauma, and Loss examines recent Mexican historical novels that highlight the mistakes of the nineteenth century for the purpose of responding to present crises.